Stereotactic Body Radiotherapy with Cyberknife for Cardiac Malignancies. Issue 3 (May 2015) - Bonomo, Pierluigi; Cipressi, Samantha; Desideri, Isacco; Masi, Laura; Doro, Raffaela; Iermano, Carmine; Greto, Daniela; Simontacchi, Gabriele; Mangoni, Monica; Paiar, Fabiola; Meattini, Icro; Scoccianti, Silvia; et al.
Aims and Background: Radiobiological and technical considerations have traditionally limited the role of radiation therapy in the context of primary and secondary cardiac malignancies. Stereotactic body radiotherapy (SBRT) is a promising modality for the delivery of focused high-dose radiation with ablative potential to complex targets such as small, deep-seated, moving lesions, allowing also for re-irradiation. Methods: Between January 2013 and October 2013, 3 patients underwent SBRT for cardiac lesions: 2 patients had recurrent, previously irradiated cardiac angiosarcomas (PCA) and 1 patient had a cardiac metastasis from melanoma. They were treated with fiducial-guided robotic radiotherapy with CyberKnife. As for dose prescription, 24 Gy in 3 fractions (80% isodose) and 30 Gy in 5 fractions (80% isodose) were administered to the recurrent PCAs and cardiac metastasis, respectively. Results: At 2 months after SBRT, cardiac MRI showed a partial response in the patients treated for recurrent PCA while the cardiac metastasis remained stable. In all cases, absence of local progression was subsequently confirmed by contrast-enhanced cardiac MRI after 6 months, without any evidence of treatment-related side effects. Conclusions: Fiducial-guided SBRT proved to be feasible and effective in preventing local disease progression in selected patients with cardiac malignancies.